Unflued gas heaters and respiratory symptoms in older people with asthma. Issue 4 (16th January 2012) - Franklin, P J; Loveday, J; Cook, A
Abstract : Background: Unflued gas heaters (UFGHs) and cookers are a major contributor to air pollution in homes. Gas appliances have been associated with adverse respiratory outcomes in children and, less consistently, adults. There have been very few studies on the effects of gas appliances on the respiratory health of older people. Objectives: This study investigated the daily lung function and respiratory symptoms of older people (>55 years of age) who did and did not use an UFGH as a primary source of heating. Methods: 71 patients with asthma were recruited for the study. Each patient participated for one 12-week winter period. All patients recorded daytime and night-time symptoms in a diary and completed morning and evening peak flow and forced expiratory volume in 1 s for the study period. General estimating equations were used to measure the associations between symptoms and lung function outcomes and same and previous day (lag 1) UFGH exposure. Results: Same and previous day (lag 1) UFGH exposure was associated with significantly increased ORs for wheeze and dyspnoea compared with days on which no heating was used. Furthermore, there were significant increases in the average odds of reported wheeze and dyspnoea per hour of UFGH heater use. Small but significant reductions in morning to evening peak flow and forced expiratory volume in 1 s were observed on the days an UFGH was used compared with days when other heating was used or there was no heating. Conclusion: Exposure to UFGHs may have a detrimental effect on symptoms and lung function in older people with mild to moderate asthma.